Corpo e Educação Física: as representações simbólicas dos discentes de Educação Física do ICSEZ-UFAM. - Silva, Toniel Costa (Brasil, 2023)
The field of study of this work were the representations of the body/cultural body among the students of the Physical Education course UFAM/ICSEZ. The objective of the research was to understand the changes in the symbolic representations of the body and body culture from the perspective of students of the Physical Education course at ICSEZ/UFAM during their academic training. Thus, it was based on the assumption that body culture consists of a formulation that aims to “account for” the different modalities of body movement that humanity has historically produced and systematized: dance, fight, game, gymnastics, mime, capoeira and sport. (SOARES et al., 1993, p.42). The question that guided our research was the following: What symbolic representation of body/body culture do Physical Education students from ICSEZ/UFAM adopt in their daily lives? Are there changes or a new meaning about the expression of the body/body culture of Physical Education students at ICSEZ/UFAM in the face of their academic-professional experiences throughout the professional training process? The study was carried out at the Instituto de Ciências Sociais, Educação e Zootecnia – ICSEZ – UFAM, based on information collected from the students of the 3rd, 5th and 7th periods of the Physical Education Degree Course in two moments, the initial moment being the period from August to November 2019 (moment 1) and April and May 2022 (moment 2). Qualitative research (Andrade, 2002) was adopted as a methodological path, using standardized techniques for data collection, such as: semi-open interviews and a pre-formulated questionnaire, in order to identify which representations and meanings about the body/body culture academics from the Physical Education/ICSEZ course elaborated during the course. The analysis process consisted of the interpretation of the collected data where the connection between the results obtained with others already known was established. The information was collected from the questionnaire and was interpreted from the Content Analysis methodology. The results showed that the students, before entering the course, had a biologicist and mechanistic view of the body; this meaning was changing, but the mechanism continued after the course. The understanding of body culture had a new meaning, according to the speeches of the students; however, there is a caveat that the theme should be given more emphasis in the course disciplines, thus opening up a range of possibilities for understanding the body.